2006
DOI: 10.1007/s10725-006-9148-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro embryo rescue culture of F1 progenies from crosses between diploid and tetraploid grape varieties

Abstract: The purpose of this study was to understand factors affecting in vitro embryo rescue culture from hybrids between diploid and tetraploid varieties of grape in creation new triploid germplasm resources. The effects of different media, removal ages of immature seeds and reciprocal crosses of parents on the germination and seedling survival of immature seeds from crosses between diploid and tetraploid grape varieties by in vitro embryo rescue culture were investigated. The results indicated that the medium consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 12 publications
0
31
0
2
Order By: Relevance
“…Also [11], by using the technique of rescue of immature embryos as a tool for the gene introgression in varieties of vine, obtained satisfactory results, had achieved 26.7% of rescued embryos in the "Emerald Seedless" variety, with a percentage of developed seedlings in about 19.6% after 60 days of cultivation. On the other hand, the results obtained by [12] when realizing the study about embryo in crosses of diploid and tetraploid vine varieties, had determined to be between 35 -45 days the best period to remove the embryos of the seed-traits. In the present study, it was observed that the 60 days period after seeds inoculation resulted in an increased number of embryos produced, as well as in better characterized developmental stages with higher germination values.…”
Section: Resultsmentioning
confidence: 99%
“…Also [11], by using the technique of rescue of immature embryos as a tool for the gene introgression in varieties of vine, obtained satisfactory results, had achieved 26.7% of rescued embryos in the "Emerald Seedless" variety, with a percentage of developed seedlings in about 19.6% after 60 days of cultivation. On the other hand, the results obtained by [12] when realizing the study about embryo in crosses of diploid and tetraploid vine varieties, had determined to be between 35 -45 days the best period to remove the embryos of the seed-traits. In the present study, it was observed that the 60 days period after seeds inoculation resulted in an increased number of embryos produced, as well as in better characterized developmental stages with higher germination values.…”
Section: Resultsmentioning
confidence: 99%
“…Для преодоления эмбриональной несовмести-мости применим метод «спасения зародышей» (embryo rescue techniques), предусматривающий их своевременное вычленение и культивирование in vitro. Сроки и способы вычленения гибридных зародышей, состав питательных сред и условия культивирования зависят от таксономиче-ской принадлежности скрещиваемых видов (Kruse, 1974;Pershina et al, 1998;Yang et al, 2007). Впервые этот метод был использован для культивирования гибридных заро-дышей льна (Laibach, 1925) и применяется для получения гибридов F 1 многих культур, в том числе злаковых (Kruse, 1974;Pershina et al, 1998;Moreno et al, 2014), овощных (Geerts et al, 2011), цитрусовых (Aleza et al, 2012), вино-града (Li et al, 2014a) …”
Section: эмбриональная несовместимость и возможности ее преодоленияunclassified
“…These two factors may be far more important than culture conditions or culture media. Finally, the ploidy of both seed and pollen parent, can have an effect on the outcome of interspecific hybridizations [23,21].…”
Section: Identification Of the Time And Type Of Barrier In Hybridizationmentioning
confidence: 99%